Case Report: Primary osteosarcoma of the kidney - Chen, Junyong; Liao, Hongxian; Zhan, Rungen; Zheng, Qiaoli; Deng, Jian; Wang, Guojie; Zhang, Jie (Frontiers in Oncology, 2023)
Extraosseous osteosarcoma is a rare malignant tumor, most commonly occurring in the thigh, upper limbs, and retroperitoneum. However, there are only a few reported cases of renal osteosarcoma. Herein, we present the case of a 54-year-old woman with malignant extraosseous osteosarcoma of the left kidney. CT and MR imaging revealed a soft tissue mass originating from the left kidney.